How can impact strategies be developed that better support universities to address twenty-first-century challenges?. (22nd November 2022) - Reed, Mark S.; Gent, Saskia; Seballos, Fran; Glass, Jayne; Hansda, Regina; Fischer-Møller, Mads
Abstract : page_1 other To better address twenty-first-century challenges, research institutions often develop and publish research impact strategies, but as a tool, impact strategies are poorly understood. This study provides the first formal analysis of impact strategies from the UK, Canada, Australia, Denmark, New Zealand and Hong Kong, China, and from independent research institutes. Two types of strategy emerged. First, 'achieving impact' strategies tended to be bottom-up and co-productive, with a strong emphasis on partnerships and engagement, but they were more likely to target specific beneficiaries with structured implementation plans, use boundary organisations to co-produce research and impact, and recognise page_2 other impact with less reliance on extrinsic incentives. Second, 'enabling impact' strategies were more top-down and incentive-driven, developed to build impact capacity and culture across an institution, faculty or centre, with a strong focus on partnerships and engagement, and they invested in dedicated impact teams and academic impact roles, supported by extrinsic incentives including promotion criteria. This typology offers a new way to categorise, analyse and understand research impact strategies, alongside insights that may be used by practitioners to guide the design of future strategies, considering the limitations of top-down, incentive-driven approaches versus more bottom-up, co-productive approaches.